NILAI USWATUN HASANAH (KETELADANAN) SEBAGAI FONDASI IMPLEMENTASI KURIKULUM BERBASIS CINTA DI MADRASAH: KAJIAN KEPUSTAKAAN - Alfadhli; Musli; Della Amrina Yusra; Akmalun Najmi; Thaharoh Ananda Mumtahana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic education in the modern era faces multidimensional challenges related to rapid social, cultural, and technological changes. This situation demands a more humanistic, relevant, and character-building educational approach. In this context, Islamic educational institutions have a strategic responsibility to instill the values ​​of faith, noble morals, and social empathy. This study aims to examine the role of exemplary behavior (uswatun hasanah) as the foundation for the implementation of the Love Based Curriculum developed by the Ministry of Religious Affairs of the Republic of Indonesia. This study used a qualitative method with a library research approach. Data collection techniques were carried out through a systematic review of books, scientific journal articles, policy documents, and relevant previous research results. Data analysis was carried out through data reduction, categorization, thematic interpretation, and drawing conclusions. Data validity was tested through triangulation of sources and theories, as well as checking the consistency of arguments. The results show that teacher role models are a determining factor in the successful implementation of the Love Based Curriculum. The integration of good moral values, based on the exemplary behavior of the Prophet Muhammad (uswatun hasanah), can shape the character of students to be religious, humanistic, and empathetic, in line with the vision of developing perfect human beings in Islamic education.